Utility of the Whole Genome Sequencing based methodologies in routine European tuberculosis reference laboratory network setting. (May 2022) - Holicka, Yen; Tagliani, Elisa; Cirillo, Daniela Maria; Nikolayevskyy, Vlad
Abstract: This study aims to gather observational evidence of Whole Genome Sequencing's (WGS) impact in the pathogen identification, antimicrobial resistance profiling and transmission tracking from its users' observation within the diagnostic setting of the European reference laboratories for tuberculosis. Sixteen laboratories that have been utilising WGS in their tuberculosis diagnostic laboratory were invited and twelve (75%) responded to our online questionnaire. Key findings include its primary utilisation for drug resistance prediction and epidemiological services; Mtb surveillance and outbreak investigation. 92% reported significant improvements to the performance of TB drug resistance testing and the reduction of false clustering. Despite the public health benefits of the WGS technology was largely positive in non-tuberculous mycobacteria disease management, multidrug-resistant TB patient management, reputational aspects and turnaround times, further studies are required to review the financial impact as various regulations and service aspects have added to the complexity to disentangle this aspect.